A new highland species of treefrog of the Dendropsophus columbianus group (Anura: Hylidae) from the Andes of Colombia - Rivera-Correa, Mauricio; Gutiérrez-Cárdenas, Paul David Alfonso (Zootaxa, 2012)
A new species of tree frog of the genus Dendropsophus is described from the highlands of the Cordillera Central of theAndes, departamento de Antioquia, Colombia (06º58’50’’N, 75º08’07’’W, 1700 m a.s.l.). Dendropsophus norandinus sp.nov. differs from other Andean Dendropsophus previously described by the following combination of traits: dorsal skinsmooth with minute scattered tubercles; axillary membrane developed; distal subarticular tubercle of fourth finger bifid;ventral surfaces cream with variable brown markings on gula, throat, and outer region of belly; medial area of the bellyimmaculate; in life axilla and groin pale yellow in males and bright orange in females; toe webbing extensive [I (1–1+ )–(11/2–13/4 ) II 1–(2–2- ) III 1–(2–2- ) IV (2–2- )–1 V], and tadpoles with tooth row formula of 0/2. On the basis of morphologicalsimilarities, principally between tadpoles, we tentatively assign this new species to the Dendropsophus columbianus group.